2016
DOI: 10.15537/smj.2016.7.14261
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical consequences of occupational exposure to blood and other body fluids in a university hospital in Saudi Arabia

Abstract: Objectives:To describe the epidemiological characteristics, clinical impact, and adequacy of post-exposure management of occupational exposure to blood and body fluids (BBFs).Methods:Retrospective chart review of individuals reporting exposure to BBFs from 2007 to 2013 at King Abdulaziz University Hospital, Jeddah, Kingdom of Saudi Arabia.Results:The total number of exposures reported was 326 exposures, of which 302 (92.6%) exposures were percutaneous, 21 (6.5%), mucocutaneous, and 3 (0.9%), bites. Nursing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
6
17
3
1
Order By: Relevance
“…Our findings indicate that about half of the healthcare workers had been exposed to HIV infection at their duty posts at one time or another in the past one year prior to this study. These findings are consistent and similar to the Bosnia/Herzegovinian, Cameroonian, Saudi Arabian studies on risk of occupational exposure conducted [9][12] [13]. On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [14].But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [8] ,Kuwait [15] , South Korea [16] and Northern Nigeria [17].This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings indicate that about half of the healthcare workers had been exposed to HIV infection at their duty posts at one time or another in the past one year prior to this study. These findings are consistent and similar to the Bosnia/Herzegovinian, Cameroonian, Saudi Arabian studies on risk of occupational exposure conducted [9][12] [13]. On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [14].But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [8] ,Kuwait [15] , South Korea [16] and Northern Nigeria [17].This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques.…”
Section: Discussionsupporting
confidence: 88%
“…Contact with potentially infectious body fluid in both private and public facilities was found to be the commonest route of exposure to HIV infection in this study and it represents a substantive means of HIV transmission to a healthcare worker [19]. However, this finding is different from other studies where sharp injuries were found to be the commonest [13]. This outcome may be due to the fact that activities relating to dealing with sharps are more common among healthcare workers compared to dealing with activities that may cause splashes from body fluids.…”
Section: Discussioncontrasting
confidence: 76%
“…Our findings indicate that about half of the healthcare workers had been exposed to HIV infection at their duty posts at one time or the other in the past one year prior this study. These findings are consistent and similar to the Bosnia/Herzegovinian, Cameroonian, Saudi Arabian studies on risk of occupational exposure conducted [9][12] [13]. On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [14].But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [8] ,Kuwait [15] , South Korea [16] and Northern Nigeria [17].This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques.…”
Section: Discussionsupporting
confidence: 88%
“…Considering that a single occupational exposure, as well as biological risk may cause other psychological consequences, 12,13 this study aimed to track PTSD symptoms according to the Impact of Event Scale-Revised (IES-R) scores in nursing staff exposed to a PCBM accident in the period from October 2014 to May 2016 in a philanthropic hospital in Minas Gerais.…”
Section: -5mentioning
confidence: 99%